African art and agency in the workshop - Kasfir, Sidney Littlefield; Förster, Till (African expressive cultures., 2013)
The role of the workshop in the creation of African art is the subject of this revelatory book. In the group setting of the workshop, innovation and imitation collide, artists share ideas and techniques, and creative expression flourishes. African Art and Agency from the Workshop examines the variety of workshops, from those which are politically driven or tourist oriented, to those based on historical patronage or allied to current artistic trends. Fifteen lively essays explore the impact of the workshop on the production of artists such as Zimbabwean stone sculptors, master potters from Cameroon, wood carvers from Nigeria, and others from across the continent.